Reliability and validity of clinical tests to assess posture, pain location, and cervical spine mobility in adults with neck pain and its associated disorders: Part 4. A systematic review from the cervical assessment and diagnosis research evaluation (CADRE) collaboration. (December 2018) - Lemeunier, N.; Jeoun, E.B.; Suri, M.; Tuff, T.; Shearer, H.; Mior, S.; Wong, J.J.; da Silva-Oolup, S.; Torres, P.; D'Silva, C.; Stern, P.; Yu, H.; et al.
Abstract: Purpose: To determine the reliability and validity of clinical tests to assess posture, pain location, and cervical spine mobility in adults with grades I-IV neck pain and associated disorders (NAD). Methods: We systematically searched electronic databases to update the systematic review of the Bone and Joint Decade 2000–2010 Task Force on Neck Pain and Its Associated Disorders. Eligible reliability and validity studies were critically appraised using modified versions of the QAREL and QUADAS-2 instruments, respectively. Evidence from low risk of bias studies were synthesized following best evidence synthesis principles. Results: We screened 14302 articles, critically appraised 46 studies, and found 32 low risk of bias articles (14 reliability and 18 validity studies). We found preliminary evidence of: 1) reliability of visual inspection, aided with devices (CROM and digital caliper) to assess head posture; 2) reliability and validity of soft tissue palpation to locate tender/trigger points in muscles; 3) reliability and validity of joint motion palpation to assess stiffness and pain provocation in combination; and 4) range of motion tests using visual estimation (in cervical extension only) or devices (digital caliper, goniometer, inclinometer) to assess cervical mobility. Conclusions: We found little evidence to support the reliability and validity of clinical tests to assess head posture, pain location and cervical mobility in adults with NAD grades I-III. More advanced validity studies are needed to inform the clinical utility of tests used to evaluate patients with NAD. Highlights: Few reliable and valid clinical tests to assess pain location and cervical spine mobility in adults with NAD exist. Evidence is preliminary at best, supported by phase I and II validity studies from the Sackett and Haynes classification (Sackett and Haynes, 2002 ). There is no evidence that any of the clinical tests affects clinical outcomes related to NAD.